2011
DOI: 10.5099/aj110400278
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Apoptosis and Autophagy in Human Pancreatic Cancer Cells by a Novel Synthetic C-1 Analogue of 7-deoxypancratistatin

Abstract: Pancreatic cancer is amongst the deadliest cancers in the world. It is associated with poor prognosis, is notorious for developing chemoresistance, and very few approved chemotherapeutics are available to treat this disease. The natural compound pancratistatin (PST) has shown to effectively induce cytotoxicity selectively in numerous cancer cell types. However, it is present in only minute quantities in its natural source and many complications have burdened its chemical synthesis. We have overcome these bottl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Presently, a wide variety of compounds have been discovered to perform their pharmacological effects against some diseases through inducing apoptosis in various tumor cells of human origin [26]–[28]. As of now, some modes of action induced by therapeutic drugs in the apoptotic pathways have been delineated [29][34]. Herein, we were interested in testing the effect of spiclomazine on the apoptosis-inducing of CFPAC-1 and MIA PaCa-2 in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…Presently, a wide variety of compounds have been discovered to perform their pharmacological effects against some diseases through inducing apoptosis in various tumor cells of human origin [26]–[28]. As of now, some modes of action induced by therapeutic drugs in the apoptotic pathways have been delineated [29][34]. Herein, we were interested in testing the effect of spiclomazine on the apoptosis-inducing of CFPAC-1 and MIA PaCa-2 in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…To this extent, compound 2 was able to decrease MMP, increase levels of ROS and cytochrome c in isolated mitochondria and induce autophagic effects in both cell lines [27]. As observed in the Saos-2, BxPC-3 and PANC-1 cells above [23,26], the caspase inhibitor Z-VAD-FMK (at both 25 and 50 μM) could not protect HCT116 cells from the apoptotic onslaught of compound 2 (1 μM) [27]. This confirmed the action of this alkaloid to be at the stage of mitochondrial destabilization, upstream of executioner caspase activation, which in turn caused the release of various apoptogenic factors involved in both caspase dependent and independent pathways of apoptotic induction [27].…”
mentioning
confidence: 55%
“…Caspase signaling upstream of mitochondrial membrane permeabilization, independent of mitochondria, is thus not vital for the induction of apoptosis by 2 thereby vindicating the possibility of a mitochondrial target for this alkaloid [23]. Further studies of phenanthridone (2) showed it to be very active against the pancreatic cancer cells BxPC-3 and PANC-1 at dosages of 0.1 to 2 μM [26]. It induced apoptosis selectively in these cells by targeting the mitochondria where it dissipated MMP, increased the generation of ROS and caused the release of apoptogenic factors [26].…”
mentioning
confidence: 99%
See 2 more Smart Citations